Implementation of Point-of-Care PCR-testing for the diagnosis of respiratory infections in vulnerable patient populations - Tolle, Hannah; Wachinger, Jonas; Castro, María del Mar; Morales, Ivonne; Denkinger, Claudia M. (PLOS ONE, 2025)
Background Point-of-Care (POC) PCR-testing provides accurate, and timely results in diagnosing respiratory viral infections. Despite these benefits, stakeholder perceptions and its potential for improving health outcomes remain insufficiently explored. Therefore, we aim to explore the acceptability and feasibility of POC PCR-testing implementation in settings attended by vulnerable populations. Methods We conducted semi-structured interviews with stakeholders from ambulatory settings, including decision makers, molecular diagnostics experts, healthcare workers, and patients. Study settings included two emergency departments (one adult, one pediatric), two oncology units, and two dialysis units, including both POC PCR implementors and non-implementors. We thematically analyzed our data, drawing on components of the Thematic Framework of Acceptability, the CFIR, and the Consolidated Framework for Sustainability Constructs in Healthcare. Results Stakeholders recognized COVID-19, influenza A&B, and RSV as significant healthcare challenges and generally viewed POC PCR-testing as fit to address them. Stakeholders exhibited varying levels of knowledge about POC PCR-testing, with lower levels among non-implementors. While perceived benefits included rapid results, accuracy, and automation, concerns regarding cost, workload, and device throughput remained. Stakeholders recognized testing’s clinical impact in terms of transmission prevention and patient management. Perceived infection risk, disease prevalence, governmental regulations, and funding availability further influenced implementation decisions. Implementation processes were deemed straightforward, but limited involvement in decision-making processes dissatisfied some healthcare providers. End-users valued POC PCR-devices’ ease-of-use, while molecular diagnostics experts stressed that testing should be performed by medical staff. Sustainability considerations emphasized the stepwise development of testing guidelines, adaptation to local workflows, and continuous evaluation and quality control. Conclusion POC PCR-testing for respiratory viral infections is generally accepted. Knowledge, cost, workload and perceived benefit of testing guide decisions, while testing upon suspicion is favored over screening strategies due to per-test-cost and low device throughput. Sustainability requires cost-efficiency through guidelines and outcome monitoring. While test accuracy and turnover-time are valued, clinical impact requires further investigation.
Gesehen am 26.11.2025